Self-monitoring of blood glucose in type 2 diabetics not treated with insulin - Lobo, Filipa Almada (2007)
Introduction: Self-monitorization of capillary glycemia of type 1 and type 2 diabetics in insulin therapy is effective, resulting in an improvement of the glycemic control. However, in those that do not take insulin, this procedure is controversy. The aim of this work is to conduct an evidence-based revision on the role of self-monitorization of capillary glycemia in these diabetics. Methodology: A systematic revision was conducted in MEDLINE, Cochrane Library, Bandolier, Medscape, Tripdatabase, DARE and EBM Resources, from 1989 to May 2005. Studies that evaluated the following characteristics were included: glycemic control measured by glycosylated hemoglobin (Hb A1c) and/or postprandial glycemia and/or quality of life. Eight randomized clinical trials (RCTs), two Cohort Studies, one case-control study, four meta-analysis and two evidence-based guideline were included. Results: Self-monitorization of capillary glycemia global effect showed a statistically significant reduction of 0.39% in HbA1c (CI 95% 0,56-0,21). Postprandial glycemia, evaluated by two RCTs, demonstrated a non-significant reduction with self-monitorization of capillary glycemia. No statistically significant differences were found in studies that evaluated quality of life. Discussion/Conclusion: The clinical vigilance with self-monitorization of capillary glycemia in type 2 diabetics not treated with insulin resulted in an improvement of the glycemic control. However, since the majority of the studies have a low methodological quality, its clinical applicability is limited. The results of a big and well designed RCT are expected in 2007 in order to reinforce the evidence of this recommendation.